2018
DOI: 10.1155/2018/2874160
|View full text |Cite
|
Sign up to set email alerts
|

Insecticides Resistance Status of An. gambiae in Areas of Varying Agrochemical Use in Côte D’Ivoire

Abstract: Background Insecticide resistance monitoring of the malaria vectors to different classes of insecticides is necessary for resistance management. Malaria vector control management approaches are essentially based on IRS and LLINs. However, insecticide resistance is caused by several sources of selection and in case the selection pressure is from agricultural practices, then measures need to be taken to avoid a failure of the control methods put in place. The current study was undertaken to monitor the susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
70
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 33 publications
6
70
1
Order By: Relevance
“…coluzzii [36]. Both species generally breed in fresh water pools resulting from human activities such as irrigated rice fields and vegetable gardens, which are often treated with insecticides [32,33,35,37 In this study, pre-exposure to PBO before the different pyrethroids tested showed statistically significant but still insufficient increases in the mortality of the An. gambiae s.l.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…coluzzii [36]. Both species generally breed in fresh water pools resulting from human activities such as irrigated rice fields and vegetable gardens, which are often treated with insecticides [32,33,35,37 In this study, pre-exposure to PBO before the different pyrethroids tested showed statistically significant but still insufficient increases in the mortality of the An. gambiae s.l.…”
Section: Discussionmentioning
confidence: 58%
“…A recent survey by the ministry of agriculture revealed that more than 20,000 tons of chemicals including pesticides and insecticides were applied in the country in 2018 for agricultural purposes including 40% of this amount entering illegally [34]. This likely contributed to the increasing resistance of malaria vectors to insecticides commonly used for insect control in general and malaria vector control specifically [32,33,35]. In Côte d'Ivoire, the two major malaria vectors include An.…”
Section: Discussionmentioning
confidence: 99%
“…Due to practices linked to intensification of agriculture, resistance to insecticides has emerged and spread [10]. Several studies suggest that intensive use of insecticides in agriculture selects for resistant genes in malaria vectors [11,12]. Although research has been conducted previously on farmers' knowledge, attitudes, practices and beliefs (KAPB) on insecticides used in agriculture [10,12], there is a paucity of studies on people's knowledge about resistance to currently utilized insecticides and the causes leading to resistance, including how people cope with the growing resistance.…”
Section: Introductionmentioning
confidence: 99%
“…These studies were conducted in WHO-approved experimental huts 16 in the locality of Tiassale where wild An. gambiae malaria vectors are resistant to insecticides 18,19 with human subjects sleeping under the nets each night. Three entomological parameters were measured: (i) the mean entry rate of mosquitoes per hut per night, (ii) the mean exit rate per hut each night, and (iii) the mean mortality rate per hut per night.…”
Section: Field Performance Of Gen1 Gen2 and Gen3 T-nets Against Insementioning
confidence: 99%